A Histopathological Study of Pulmonary Hypertension in Connective Tissue Disease - Nobuhito Sasaki; Akihisa Kamataki; Takashi Sawai (Allergology International, 2011)
Connective tissue diseases (CTD), such as systemic sclerosis (SSc), systemic lupus erythematosus (SLE), and mixed connective tissue disease (MCTD), develop pulmonary hypertension (PH). Generally all PH cases associated with any CTD are classified into the same PH group. However, histological examination shows both common and specific lesions for each disease. In patients with SLE, fibrosis is generally rare and mild. The findings of PH in SLE are similar to those in primary pulmonary hypertension. Many cases of SSc are accompanied by fibrosis. MCTD is rather close to SSc. Arterial and arteriolar lesions of MCTD are characterized by fibrous intimal thickening. In this review, we describe the pathological features of PH associated with each CTD.